Growth kinetics and thermodynamic stability of octadecyltrichlorosilane self-assembled monolayer on Si (100) substrate - Kulkarni, S. A.; Mirji, S. A.; Mandale, A. B.; Gupta, R. P.; Vijayamohanan, K. P. (Materials Letters, 2005)
We have studied the growth kinetics and thermodynamic stability of octadecyltrichlorosilane (OTS) self-assembled monolayers on Si (100) substrate in order to understand its role in controlling the adhesion and surface hydrophobicity. Time-dependent contact angle measurements, using water as a function of OTS concentration, show rapid monolayer formation in the initial stage followed by a slow attainment of full coverage and the overall kinetics approximately follows the Langmuir adsorption isotherm. The adsorption rate constant (k(a) = 150 M-1 s(-1)) is found to be significantly greater than the desorption rate constant (k(d) = 0.156 s(-1)) while the Gibbs free energy (Delta G(ads)) change amounts to -4.2 kcal/mol suggesting thermodynamic stability of OTS monolayer on a silicon surface. Partial monolayer formation by a `uniform' growth mechanism, even at low coverage, is revealed by atomic force microscopy (AFM) in conjunction with grazing angle FTIR spectroscopy. Analysis of the interfacial adhesion properties using Zisman plot suggests a critical surface tension (gamma(c)) of 20.7 dyn/cm for OTS monolayer on Si (100) surface. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Gibbs's free energy (AG); growth kinetics; octadecyltrichlorosilane (OTS); self-assembled monolayers (SAMs); Zisman plot

Adsorption of methanol on Si(100)/SiO(2)and mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Ravi, V.; Jacob, Nalini E.; Patil, K. R. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of methanol on SiO(100)/SiO2 substrate and mesoporous SBA-15 has been studied by using Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is employed to study the adsorption kinetics of methanol on SiO(100)/SiO2 and thermal stability of adlayer. Thermogravimetric (TGA) technique is used to understand the thermal behavior of methanol layer on SBA-15. Adsorption kinetics fit fairly well with Langmuir isotherms giving adsorption rate constant, k(a) = 0.0021 W s(-1). FTIR results show formation of methoxy silicon (SiOCHA silicon polyhydride (SiH2), carboxylate, molecular water and hydroxyl groups on Si(100)/SiO2 surface and only methoxy silicon on SBA-15. XPS results confirm methanol adsorption and support FTIR results. The methanol adlayers are found to be thermally stable up to a temperature of similar to 262 degrees C on both Si(100)/SiO2 and SBA-15 and decompose between 262 and 450 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; desorption; kinetics; Methanol; SBA-15; Si(100)/SiO2; thermal stability

Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability

Adsorption of octadecyltrichlorosilane on Si(100)/SiO2 and SBA-15 - Mirji, S. A. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on Si(100)/SiO2 substrate and mesoporous SBA-15 has been studied by energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is used to study the adsorption kinetics of OTS on Si(100)/SiO2 and thermal stability of adsorbed OTS layer. Thermogravirnetric (TGA) technique is employed to understand the thermal behavior of OTS adlayer on SBA-15. Langmuir isotherms fit very well with OTS adsorption kinetics data on Si(100)/SiO2 and furnish adsorption rate constant, k(a) = 236 M-1 s(-1), desorption rateconstant, k(d) = 0.0082s(-1) and Gibbs free energy of adsorption, Delta G(ads) = -6.28 kcal mol(-1). EDAX and XPS results both show increased carbon content due to OTS adsorption and decreased oxygen and silicon content due to screening of these elements by OTS adlayer. FTIR data shows methylene (-CH2) and methyl (-CH3) stretching bands, in close agreement with reported data. The OTS layers are found to be thermally. stable up to a temperature of approximate to 260 degrees C on both Si(100)/SiO2 and SBA-15. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Gibbs free energy; OTS; SBA-15; Self-assembly; Si(100)/SiO2; thermal stability

Adsorption of methanol on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B. (Materials Letter, 2007)
The adsorption of methanol onmesoporous SBA-15 has been studiedbyrising Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoclectrom spectroscopy (XPS) and tbennogravimettic analysis (TGA). The BET surface area analysis shows decreases of the surface area from 387 to 383 m(2)/g, pore volume from 0.88 to 0.81 cm(3)/g and pore diameter from 9.07 to 8.4 mm after methanol adsorption. The appearance of strong IR bands at 2862 and 2964cm(-1) due to methyl (-CH3) symmetric and asymmetric stretching demonstrate the presence of methanol and evidence of successful methanol adsorption. XPS results show increase of carbon and oxygen content on the surface of SBA-15. Thermogravirriettic analysis shows that the methanol adsorbed on SBA-15 is stable up to a temperature of 265 degrees C and that the methanol adlayers decompose between 265 and 588 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Electron microscopy; Methanol; SBA-15; Surfaces; thermal stability

Novel technique to prepare LiNbO3 at low temperature - Samuel, V.; Gaikwad, A. B.; Jadhav, A. D.; Mirji, S. A.; Ravi, V. (Materials Letter, 2007)
Fresh niobium hydroxide was first precipitated from NbF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing lithium and niobium hydroxides together and heating at a low temperature (400 degrees C) produced pure ultrafine single phase LiNbO3 (LN). In the literature, this is the lowest temperature so far reported on the formation of LN. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by transmission electron microscopy (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; LiNbO3; X-ray diffraction

Low temperature synthesis and characterization of BiNbO4 powders - Radha, R.; Muthurajan, H.; Rao, N. Koteswara; Pradhan, Sivaram; Gupta, U. N.; Jha, Ratnesh Kumar; Mirji, S. A.; Ravi, V. (Materials Characterization, 2008)
BiNbO4 powders, a potential microwave dielectric ceramic were prepared by both coprecipitation and solid state techniques. In the former method, an aqueous ammonium hydroxide was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. It is observed that the co-precipitation produces BiNbO4 phase on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the case of solid state method. The phase contents and lattice parameters were studied by powder X-ray diffraction. The sequence of the reaction and phase evolution of BiNbO4 were also studied by the X-ray diffraction. The samples were characterized by the differential-thermal/thermo-gravimetric analyses and scanning electron microscopy techniques. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Novel hydroxide precursors for low temperature synthesis of selected ternary oxides - Muthurajan, H.; Rao, N. Koteswara; Gupta, U. N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Kumar, H. H.; Mirji, S. A.; Ravi, V. (Materials Research Bulletin, 2008)
A novel method of using hydroxide precursors to reduce the synthesis temperature for few selected ternary oxides has been presented here. This technique is very useful and advantageous when the ternary oxides contain an alkaline earth element. The selected compositions for this method are BaCeO3 (BC), BaBiO3 (BB), La0.7Sr0.3CoO3 (LSCO) and BaBi2Nb2O9 (BBN). Commercially purchased strontium (or barium) hydroxide and freshly prepared lanthanum, cobalt, bismuth and niobium hydroxides were mixed thoroughly in stoichiometric ratio and heated at different temperatures ranging from 100 to 700 degrees C for 10 h for corresponding compositions. The sequence of the reaction and evolution of the product phase were studied by the X-ray diffraction (XRD) studies. The phase purity and lattice parameters were also determined by XRD investigations. All the product phases in each case were formed at relatively low temperature than when they were prepared by co-precipitation or solid state method. The morphology and average particle size of these powders were investigated by scanning electron microscopy (SEM). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Biosynthesis of silver nanoparticles by using ganoderma-mushroom extract - Ekar, S. U.; Khollam, Y. B.; Koinkar, Pankaj M.; Mirji, S. A.; Mane, R. S.; Naushad, M.; Jadhav, S. S. (Modern Physics Letters B, 2015)
Present study reports the biochemical synthesis of silver nanoparticles (Ag-NPs) from aqueous medium by using the extract of medicinal mushroom Ganoderma, as a reducing and stabilizing agents. The Ag-NPs are prepared at room temperature by the reduction of Ag+ to Ag in aqueous solution of AgNO3. The resultant particles are characterized by using UV-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy and transmission electron microscopy (TEM) measurement techniques. The formation of Ag-NPs is confirmed by recording the UV-visible absorption spectra for surface plasmon resonance (SPR) where peak around 427 nm. The prominent changes observed in FTIR spectra supported the reduction of Ag+ to Ag. The morphological features of Ag-NPs are evaluated from HRTEM. The spherical Ag-NPs are observed in transmission electron microscopy (TEM) studies. The particle size distribution is found to be nearly uniform with average particle size of 2 nm. The Ag-NPs aged for 15, 30, 60 and 120 days showed no profound effect on the position of SPR peak in UV-visible studies, indicating the protecting/capping ability of medicinal mushroom Ganoderma in the synthesis of AgNPs.
Keywords: Biosynthesis; Ganoderma; medicinal mushroom; silver nanoparticles; UV-visible spectroscopy